Role of valproic acid and allopurinol in neuroprotection after cardiac surgery on Bangladeshi patients - Khan, Omar Sadeque; Hoque, Rezwannul; Rahman, Mostafizur; Imtiaz, Nasif (International Surgery Journal, 2022)
Background: Neurological complications are very much common after cardiac surgery in postoperative setting in Bangladesh. However, we are dealing these complications in our day-to-day practice and it costs money, longer hospital stays and admissions to rehabilitation facilities. The aim of the study was to evaluate the effectiveness of sodium valproic acid and allopurinol in preventing neurological injury following cardiac surgery with cardiopulmonary bypass. Methods: This cross-sectional study was conducted by the department of cardiac surgery, Bangabandhu Sheikh Mujib medical university (BSMMU), Dhaka, Bangladesh from January 2019 to June 2021. Total 70 patients were included and divided into two groups (36 patients with sodium valproic acid and allopurinol in group A and 34 patients without sodium valproic acid and allopurinol in group B). 10 patients were dropped out. As these two drugs were FDA approved was used per-orally for 5 perioperative days (2 days prior surgery, 1 day in operation day, 2 days postoperatively). Collected data were entered, checked and edited (to remove the outliers) with the help of the statistical package for social sciences (SPSS) software, version 26 and analyzed. Results: The intervention group (group A) had maximum survival rate (no mortality) less ICU stay, less hospital stay, early intubation, no neurological injury (p<0.05). On the contrary group B (no intervention) had 6 mortalities, several mild to moderate neurological injury, more ICU and hospital stay and morbidity. Conclusions: Sodium valproic acid and allopurinol gives neuroprotection in on-pump cardiac surgical patients. So, these two medicines can be prescribed prophylactically on individual basis.